Empowerment of Beneficiary Families of the Family Hope Program in Poverty Alleviation through Independent Graduation - Januaris, Wiwin; Ishaq, M.; Purnamasari, Ica (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
Poncokusumo Village, which is an independent village, has a paradox with the high number of social assistance recipients, especially the Family Hope Program (PKH). This phenomenon encourages the implementation of a community service program to encourage Beneficiary Families (KPM) to graduate independently in a sustainable manner. This community service aims to increase the economic and social capacity of KPM through a participatory approach based on local potential. The method used is Participatory Action Research (PAR), which actively involves KPM in the process of identifying problems, planning, implementing, and evaluating the program. The activities carried out include entrepreneurship training, strengthening KUBE institutions, integration of empowerment programs (Jatim Puspa and PENA), and intensive mentoring based on a humanistic and persuasive approach. The results show that KPM experienced an increase in knowledge, skills, and motivation to be economically independent. Some of them succeeded in graduating independently and running businesses sustainably. The conclusion of this activity confirms that participatory, contextual, and integrated empowerment can be an effective strategy in encouraging independent graduation of KPM. The contribution of this community service lies in the development of a holistic empowerment model that can be replicated in other areas with similar characteristics.